PTH-200 Amino acid profiles in patient with intestinal failure: preliminary data on biochemical insights. (22nd June 2015) - Fragkos, KC; Samaan, M; Morgan, S; Barnova, I; Smith, L; Babington, M; Patel, PS; Keane, N; Rahman, F; Di Caro, S
Abstract : Introduction: Amino acid profiles have become increasingly important in intestinal failure (IF), ever since citrulline has been used as an IF marker. The purpose of the present study is to investigate levels in patients with IF needing parenteral nutrition (PN) and to examine their use as markers of IF severity to guide clinical decisions. Method: Serum amino acids levels were measured prospectively within the cohort of patients managed by the IF Unit at our hospital using Ion Exchange Chromatography. Statistical analysis was performed by R and SPSS 21.0 using Pearson's Correlation coefficient, t-tests and ANOVA. The traditional classification of IF 1 was taken as a proxy of IF severity where Type 1 IF was coded as 1 and type 3 IF was coded as 3. Results: Our study included 35 patients (11 Males, mean age 45, range 16–87), non IF controls (n = 10), Type 1 IF (n = 3), Type 2 IF (n = 3), Type 3 IF (n = 19); all IF patients were on PN. Causes of IF were short bowel syndrome, enterocutaneous fistula, high stoma output, pseudo-obstruction and radiation enteropathy. Citrulline was significantly lower in patients with Type 3 IF (p = 0.033) and receiving PN (p = 0.031) compared to other groups. Valine was significantly lower in patients with Type 3 and 2 IF compared to other controls and type 1 (p = 0.053); a trend was observed for lower homocysteine in patients receiving PN (p = 0.082). The other amino acids didn't display differences with respects to groups. Figure 1 shows the correlation matrix between amino acids levels and severity of IF. Lower levels of citrulline, valine, alanine, total homocysteine, methionine, histidine, ornithine, and isoleucine were associated with more severe IF (range of correlation coefficients –0.432 to –0.174) whilst glutamate levels had a positive association (0.215) with less severe IF. Strong positive associations were found between amino acids valine, histidine, threonine, methionine, ornithine, alanine, leucine and isoleucine (correlation coefficient range 0.41–0.73), suggesting involvement in common biochemical pathways. Conclusion: The present study confirmed the usefulness of citrulline as a marker of enterocytes mass in IF It provided new evidence that lower levels of valine, total homocysteine, methionine, histidine, ornithine, and isoleucine were associated with more severe IF. Larger studies are needed to validate those data. Disclosure of interest: None Declared. Reference: ESPEN endorsed recommendations. Definition and classification of intestinal failure in adults. Clin Nutr . 2014. doi: 10.1016/j.clnu.2014.08.017